Development of an educational game about cervical cancer and its forms of prevention (Research, Society and Development, 2022)
The present study aims to develop an educational game about cervical cancer and its forms of prevention. This is a methodological research guided by the referential of Pasquali (2010) composed by the theoretical, empirical (experimental) and analytical poles; in the theoretical pole, an integrative literature review was carried out; in the empirical (experimental) the dynamics and content of the educational tool was structured; in the analytical pole, the instrument was validated by specialists and by descriptive statistics. The game was titled “Unraveling Cervical Cancer”, consisting of 32 cards, 16 have affirmative sentences and 16 images corresponding to each affirmative. No specialist evaluated the items with “disagree”, giving a content validation index of 1.0, being, therefore, successfully validated. The items that were evaluated as “partially agree” were reformulated according to the experts' suggestions. An educational tool was built and validated that proved to be adequate and viable for the guidance of women about cervical cancer and its forms of prevention.